Research on Biomarkers of Different Growth Periods and Different Drying Processes of Citrus wilsonii Tanaka Based on Plant Metabolomics - Yan, Hui; Pu, Zong-Jin; Zhang, Zhen-Yu; Zhou, Gui-Sheng; Zou, Dong-Qian; Guo, Sheng; Li, Chao; Zhan, Zhi-Lai; Duan, Jin-Ao (Frontiers in Plant Science, 2021)
Fruit of Citrus wilsonii Tanaka called “Xiang yuan” in Chinese, means fragrant, round. It was widely used in the pharmaceutical and food industries. This fruit has well-known health benefits, such as antioxidant, radical scavenging, and anti-inflammatory. Naringin, deacetylnomilin, citric acid, limonin, and nomilin were the characteristic components of Citrus wilsonii Tanaka. Although the fruit of Citrus wilsonii Tanaka possessed many applications, there was a lack of research on the growth period and drying process. In this study, plant metabolomics was used to analyze the biomarkers of the growth period, appearance indicators and metabolites abundance were combined for analysis of change regularities of the growth period. The representative differential metabolites of naringin, citric acid and limonin were screened out, and the abundance of these components were relatively highest in the middle of the growth period. Therefore, the fruit of Citrus wilsonii Tanaka should be harvested before it turned yellow completely, which could effectively ensure the content of potential active ingredients. In the comparison of different drying methods, citric acid and naringin were considered to be representative differential components, but limonoids were relatively stable and not easily affected by drying methods. Naringin was an index component that could not only reflected the maturity but also related to different drying methods. Considering its physical and chemical properties and its position, naringin had the potential to be a biomarker of Citrus wilsonii Tanaka.